2015
DOI: 10.4028/www.scientific.net/msf.816.594
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mo Addition on the Grain Growth of IN718 Alloy

Abstract: The effect of Mo addition on the grain growth of Inconel 718 alloy has been investigated. It was revealed that δ phase was precipitated at the grain boundaries when the Mo addition is in the range of 2.80% - 4.00%, while the Mo-bearing phase was precipitated at the grain boundaries when the Mo addition is in the range of 5.50% - 7.50%. By pinning the grain boundary, the grain boundary precipitate can effectively prevent the grain growths. So the grains grow rapidly with increase the solution temperature when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Additionally, 316L ASS in this work has a high content of molybdenum, but it was not sufficient to suppress grain growth compared to 253 MA ASS during annealing. Han et al (2015) found that molybdenum at around 2 wt% in IN718 alloy could precipitate in austenite grain boundaries, which effectively prevented grain growth. Grain growth is also affected by the SFE values in both steels.…”
Section: Grain Growth Of 253 Ma and 316l Assmentioning
confidence: 99%
“…Additionally, 316L ASS in this work has a high content of molybdenum, but it was not sufficient to suppress grain growth compared to 253 MA ASS during annealing. Han et al (2015) found that molybdenum at around 2 wt% in IN718 alloy could precipitate in austenite grain boundaries, which effectively prevented grain growth. Grain growth is also affected by the SFE values in both steels.…”
Section: Grain Growth Of 253 Ma and 316l Assmentioning
confidence: 99%
“…The UTS of liquid nitrogencooled FM1 fusion zone (1038 MPa) was higher than that of the FM2 fusion zone (1005 MPa) for the same weld cooling rate (510°C/s). This could be due to the reduced grain growth by the retention of molybdenum in the dendrite [11]. The microstructures were refined in FM1 fusion zone due to the addition of molybdenum which promoted solutal undercooling by the concentration gradient.…”
Section: Mechanical Property Characterization Of Weldmentsmentioning
confidence: 99%